2016
DOI: 10.1007/s40846-016-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of Short-Time MSE in Assessing Impact of Acupuncture on Peripheral Blood Flow and Autonomic Activities in Normal and Overweight Subjects

Abstract: Zusanli (ST-36) is one of the four most important acupoints in traditional Chinese medicine because it is believed to co-ordinate the functions of the immunological and gastrointestinal systems. We test the hypothesis that acupuncture at Zusanli may have significant impact on peripheral blood flow and autonomic activities by computing the area under the pulse volume curves and heart rate variability from data acquired through non-invasive approaches of eight-channel photoplethysmography and electrocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Consistently, the current study showed that acupuncture could boost peripheral perfusion as previously reported [ 36 , 37 ]. Nevertheless, combination of acupuncture and FIR had no additional benefit in terms of increasing peripheral blood flow in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, the current study showed that acupuncture could boost peripheral perfusion as previously reported [ 36 , 37 ]. Nevertheless, combination of acupuncture and FIR had no additional benefit in terms of increasing peripheral blood flow in this study.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the modified short-duration MSE (sMSE) proposed by Chang et al, the sMSE of 600 peripheral arterial pulse wave velocity (PWV) signals was in line with the cMSE of 1000 PWV signals in healthy individuals and in those with diabetes [6]. Furthermore, Yang et al used the sMSE of 350-400 electrocardiographic R-R intervals to evaluate the change of peripheral blood flow before and after acupuncture in healthy subjects [7].…”
Section: Introductionmentioning
confidence: 88%
“…Accordingly, the present study analyzed PPG signals using an overall MSE index (the average of scales 1-10, MSE [1][2][3][4][5][6][7][8][9][10] ) and by dividing the MSE into small scales (the average of scales 1-5, MSE [1][2][3][4][5] ) and large scales (scales 6-10, MSE 6-10 ) for inter-groups comparisons.…”
Section: The Smse Of Bilateral Fingertips Ppg Series Signalmentioning
confidence: 99%
“…A PPG signal is formed from photoelectric conversion, which reflects the change in blood vessel volume and the health of the cardiovascular system. 2,3 PPG signals express many biological information. 4 After the decomposition and reconstruction of PPG signals, a potential relationship can be studied between different PPG signal characteristics and cardiovascular health in humans.…”
Section: Introductionmentioning
confidence: 99%